2018
DOI: 10.1108/ijopm-01-2016-0052
|View full text |Cite
|
Sign up to set email alerts
|

Building bridges: boundary spanners in servitized supply chains

Abstract: Solutions provision depends on effective and efficient supply chains. Existing discourse within servitization has remained at the organisational or inter-organisational level with a limited emphasis on the role of individuals. However, supply chains are not just relationships between organisations; they are complex, inter-personal relationships that span organisational boundaries. The limited focus on boundary spanners and their interactions means that managerial roles critical for the provision of solutions r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 49 publications
0
66
0
2
Order By: Relevance
“…This complex nature of servitization that spans beyond a focal firm enhances the network's role in firm strategy and behavior and strengthens the relationships between networked actors (Bastl et al, 2012;Vendrell-Herrero et al, 2017). This is because service ecosystems, as parts of GVCs, underscore the systemic aspects of value cocreation, emphasizing service exchange and resources across interdependent actors (Koskela-Huotari et al, 2016;Vargo & Lusch, 2017), which is in line with research on product-service networks (Jaakkola & Hakanen, 2013;Reim et al, 2019) and the research on the link between servitization and supply chain management (Baines et al, 2009;Chakkol et al, 2018), both of which offer valuable insights into how service is created and delivered across and beyond organizational boundaries.…”
Section: Overview Of the Servitization Phenomenon Within And Across National Bordersmentioning
confidence: 54%
See 2 more Smart Citations
“…This complex nature of servitization that spans beyond a focal firm enhances the network's role in firm strategy and behavior and strengthens the relationships between networked actors (Bastl et al, 2012;Vendrell-Herrero et al, 2017). This is because service ecosystems, as parts of GVCs, underscore the systemic aspects of value cocreation, emphasizing service exchange and resources across interdependent actors (Koskela-Huotari et al, 2016;Vargo & Lusch, 2017), which is in line with research on product-service networks (Jaakkola & Hakanen, 2013;Reim et al, 2019) and the research on the link between servitization and supply chain management (Baines et al, 2009;Chakkol et al, 2018), both of which offer valuable insights into how service is created and delivered across and beyond organizational boundaries.…”
Section: Overview Of the Servitization Phenomenon Within And Across National Bordersmentioning
confidence: 54%
“…First, firms may draw on their internal product and service capabilities, which not many firms possess in totality (Ayala et al, 2019;Bastl et al, 2012;Vendrell-Herrero et al, 2017). Second, they may reach out to value chain partners, mobilize them, and deliver the servitized offering in a coordinated fashion, which is the increasingly dominant and most frequent approach yet to be fully acknowledged and investigated (Chakkol et al, 2018;Johnson et al, 2021;Raddats et al, 2019). Nonetheless, most value chains exist across national borders and signify interdependency among actors, resources, and activities in creating value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They typically are buyers in purchasing firms and sales and customer support managers of suppliers. Buyer-supplier relationships are built and sustained by individuals who span inter-organizational boundaries (Chakkol et al, 2018). Boundary spanners develop, facilitate, and sustain buyer-supplier relationships using practices such as negotiating with clients, leading innovation projects, communicating with SC partners, or contracting with suppliers (Korschun, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Other researchers have investigated TMs' contribution to the relationship established between their companies and KAs. Their findings have indicated that TMs can induce the use of customer knowledge (Salojärvi et al, 2010) to boost organizational readiness in servitization (Rabetino et al, 2017) or to create joint platforms for integrating technology into customer solutions (Chakkol et al, 2018). Another research stream has identified that TMs can help to remove internal resistance to KAM (Wilson and Woodburn, 2014) or leverage a little-formalized KAM programme (Marcos-Cuevas et al, 2014), Despite the actions performed by TMs a B2B relationship may not last forever (Kamp, 2005).…”
mentioning
confidence: 99%